Urinary placental growth factor as a predictor of complications in hypertensive disorders in pregnancy: a protocol for systematic review and meta-analysis - Marie-Claude Battista; Camille Francoeur; Julie Moreau; Samuel Lemaire-Paquette; Marie-Eve Roy-Lacroix; Anne-Marie Côté (BMJ Open)
Introduction Preeclampsia is an important cause of maternal and fetal morbidity and mortality. Although the diagnostic and prognostic values of circulating placental growth factor (PlGF) have been extensively studied, urinary PlGF represents an excellent alternative to facilitate sample collection in the follow-up of pregnant women. The aim of this study is to determine whether urinary PlGF levels throughout pregnancy can predict severe maternal, fetal/placental and neonatal complications in women with hypertensive disorders in pregnancy.Methods and analysis Studies that evaluated pregnant women with hypertensive disorders and at least one measurement of urinary PlGF will be included. Studies that measure urinary PlGF after the occurrence of the complications will be excluded. The main outcome will consist of severe maternal complications in women with hypertensive disorders in pregnancy. Secondary outcomes will consist of severe fetal/placental and neonatal complications as defined by the International Collaboration to Harmonize Outcomes for Pre-eclampsia. Prospective cohort studies and case–controls studies reporting original data will be included. Studies will be identified by searching MEDLINE and SCOPUS databases. The first literature search was conducted on 2 March 2020, and another search will be performed before analyses. All eligible studies will be assessed for risk of bias with a standardised 10-items study quality assessment tool adapted from the Study Quality Assessment tools developed by the National Institutes of Health (NIH). Summary of ORs and 95% CIs will be reported to evaluate the association between urinary PlGF levels and hypertensive disorders in pregnancy and its complications. A random-effect meta-analysis will also be performed.Ethics and dissemination Review by an ethics committee will not be required for this systematic review. This study will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and will be submitted for publication in a peer-reviewed journal as well as for presentation at conferences targeting different stakeholders, including researchers, physicians and patients.PROSPERO registration number CRD42020186313.